INFLUENCE THE HUMAN RESOURCE CAPACITY ON PERFORMANCE OF AGRICULTURAL EXTENSION OFFICERS FOR AGRICULTURAL EXTENSION INI KONAWE REGENCY - Salahuddin, Salahuddin; Rela, Iskandar Zainuddin; Malik, Nurhayu (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aimed to examine is the human resource capacity on extension officers in agricultural extension; performance of extension officers in agricultural extension; and influence the human resource capacity on the performance of agricultural officers in agricultural extension in Konawe Regency. The research sample comprised the entire population of agricultural extension officers in agricultural extension who are State Civil Apparatus (ASN) in Konawe Regency, totaling 113 individuals, with sampling conducted through a census method. The research variables consist of independent variables, namely the capacity of human resources of agricultural extension officers and dependent variables, namely the performance of agricultural extension officers in agricultural extension. Data analysis for this research employs both descriptive and inferential statistics. Descriptive statistics are utilized to outline the characteristics of the variables, where as inferential statistical analysis is employed to investigate the influences variable of capacity of human resources of agricultural extension officers on the performance of agricultural extension officers in agricultural extension. The inferential statistical technique applied in this research is Simple Regression Analysis. The results of the study showed that the human resource capacity of agricultural extension officers is in the good category. The research results also showed that the performance of agricultural extension workers is in the good category. The results of the study also show that the human resource capacity of agricultural extension officers has a significant positive effect on the performance of agricultural extension officers in agricultural extension in Konawe Regency. Increasing the capacity of human resources for agricultural extension officers will improve the performance of agricultural extension officers in agricultural extension.